PERAN MUSEUM ZOOLOGI DALAM PENELITIAN DAN KONSERVASI KEANEKARAGAMAN HAYATI (IKAN) (The Important of Museum Zoology on Research and Conservation of Biodiversity) - Arie Budiman; A. J. Arief; A. H. Tjakrawidjaya (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2002)
Indonesia is rich in fish diversity. It contains nearly 8500 species. 1300 species live in freshwater ecosystem, approximately 45 % of the world’s fish species. Habitat loss is the primary threat to Indonesia’s biological diversity. Remnant natural habitats inside and outside protected areas have come under a variety of unprecedented threats and have suffered severe and likely irreparable degradation. Freshwater ecosystems too have been subjected to intense and destructive pressures. To conserve the richness of fish diversity, more study and scientific information should be created more intense. The systematic collections of the Bogor Zoological Museum provide the scientific information and basic reference material for biodiversity inventory and monitoring in Indonesia. Improving scientific information through better reference collection and through better access to associated, habitat, geographic and environmental data is therefore an integral component of the Indonesia biodiversity conservation strategy. AbstrakIndonesia kaya akan keanekaragaman ikan, terdiri dari 8500 jenis, 1300 jenis hidup di ekosistim air tawar, merupakan 45% dari jumlah jenis global di dunia. Kehilangan habitata adalah ancaman utama bagi kekayaan keanekaragaman hayati Indonesia. Beberapa kawasan alami yang tersisasa, baik di dalam kawasan lindung ataupun di luar, menunjukan kondisi yang mengkhawatirkan, bahkan cenderung tidak dapat dipulihkan. Ekosistim perairan air tawar paling banyak mendapat tekanan. Untuk lebih mengetahui kekayaan keanekaragaman ikan, harus banyak belajar dan mencari informasi ilmiah yang lebih intensif. Koleksi sistematik di Museum Zoologi Bogor menyediakan informasi mengenai materi acuan dasar akan inventaris keanekaragaman dan monitoring di Indonesia. Museum Zoologi berperan aktif dalam menyediakan bahan acuan koleksi ilmiah dan dapat diakses, data lain yang terhimpun berupa data habitat, geografi dan lingkungan. Hal tersebut merupakana suatu komponen yang terintegrasi dari strategi konservasi keanekaragaman hayati Indonesia.